The von Hippel-Lindau Chuvash mutation in mice alters cardiac substrate and high energy phosphate metabolism - Slingo, Mary; Cole, Mark; Carr, Carolyn; Curtis, Mary K.; Dodd, Michael; Giles, Lucia; Heather, Lisa C.; Tyler, Damian; Clarke, Kieran; Robbins, Peter A. (American Physiological Society, 2016)
Hypoxia-inducible factor (HIF) appears to function as a global master regulator of cellular and systemic responses to hypoxia. HIF-pathway manipulation is of therapeutic interest, however global, systemic upregulation of HIF may have as yet unknown effects on multiple processes. We utilized a mouse model of Chuvash polycythemia (CP), a rare genetic disorder which modestly increases expression of HIF target genes in normoxia, to understand what these effects might be within the heart.